Uji Daya Hambat Ekstrak Etanol Daun Waru (Hibiscus tiliaceus) terhadap Jamur Candida albicans pada Basis Akrilik - Lumban Gaol, Anju A.; Mariati, Ni Wayan; Wahyuni , Rizka (e-GiGi, 2025)
Abstract: Removable dentures, especially the parts that come into direct contact with the mucosa, can negatively affect the oral cavity if not properly maintained, leading to chronic inflammation caused by Candida albicans known as denture stomatitis. Generally, cleaning is done mechanically or chemically by soaking in a cleaning solution. Waru plant (Hibiscus tiliaceus) is a natural material that contains active compounds such as flavonoids, saponins, alkaloids, and tannins, which have potential as antifungal agents. This study aimed to test the effectiveness of the ethanol extract of waru leaves (Hibiscus tiliaceus) against Candida albicans on an acrylic base. This was a true experimental study with a post-test control group design. The testing method used a modified Kirby-Bauer method with wells. The treatment samples were divided into concentrations of 20%, 30%, 40%, 50%, with positive and negative controls. Data were analyzed using the One-Way ANOVA test, showing p<0.05, indicating a significant difference in the mean inhibition power among the four concentration groups. The Post Hoc test (Tukey’s HSD) results showed differences in inhibition strength across each treatment concentration and the control group. In conclusion, waru leaf extract (Hibiscus tiliaceus) is effective in inhibiting the growth of Candida albicans. Keywords: dentures; dentures stomatitis; Candida albicans; Hibiscus tiliaceus Abstrak: Gigi tiruan lepasan khususnya bagian yang berkontak langsung dengan mukosa yang tidak dijaga kebersihannya akan berdampak pada rongga mulut yang disebabkan inflamasi kronis karena jamur Candida albicans dan dikenal sebagai Denture stomatitis. Secara umum pembersihan dilakukan secara mekanis atau kimiawi dengan perendaman dalam larutan pembersih. Tanaman waru Hibiscus tiliaceus merupakan bahan alami yang mengandung senyawa aktif antara lain flavonoid, saponin, alkaloid, dan tanin yang berpotensi sebagai antijamur. Penelitian ini bertujuan untuk menguji efektivitas ekstrak etanol daun waru Hibiscus tiliaceus terhadap jamur Candida albicans pada basis akrilik. Jenis penelitian ialah eksperimental murni dengan post test control group design. Metode pengujian menggunakan modifikasi Kirby-Bauer dengan sumuran. Sampel perlakuan dibagi dalam konsentrasi 20%, 30%, 40%, 50%, kontrol positif (denture cleanser polydent), dan kontrol negatif (akuades). Data hasil diuji menggunakan uji One Way ANOVA yang menunjukkan p<0,05, artinya terdapat perbedaan bermakna untuk rerata daya hambat berdasarkan keempat kelompok konsentrasi. Uji Post Hoc (Tukey’s HSD) memberikan hasil adanya perbedaan kekuatan daya hambat pada setiap konsentrasi perlakuan dan kelompok kontrol. Simpulan penelitian ini ekstrak daun waru Hibiscus tiliaceus efektif dalam menghambat pertumbuhan jamur Candida albicans. Kata kunci: gigi tiruan; denture stomatitis; Candida albicans; Hibiscus tiliaceus